The role of education and digitalization in tourism development: evidence for the European Union - Dzitac, Simona; Simut, Ramona; Badulescu, Daniel; Simut, Ciprian; Badulescu, Alina (Technological and Economic Development of Economy, 2025)
The investigation of the relationship between tourism, digitalization, education, and economic growth is increasingly significant in the context of sustainable development and technological transformation. This study examines the long run and short run impacts of digitalization (measured through internet usage and broadband subscriptions), education (reflected in tertiary enrollment and public expenditure), and macroeconomic factors (including GDP per capita, employment in services, and urbanization) on international tourism performance, as indicated by arrivals and receipts across clusters of European Union countries. Methodologically, the study adopts a two-stage approach. Hierarchical cluster analysis is first applied to classify European Union countries according to key tourism characteristics, followed by the estimation of panel ARDL models for each resulting cluster to examine both long-run equilibrium relationships and short-run dynamics. Employing panel ARDL models applied to four distinct groups of countries, the analysis highlights differentiated dynamics, strong long-run effects in high-income tourism economies and more pronounced short-run responsiveness in structurally varied countries. Cointegration tests affirm the existence of long-run relationships in most clusters, reinforcing the validity of an error correction framework. Therefore, the empirical findings indicate that digitalization exerts a consistently positive influence on tourism performance in the long-run, while the effects of education are more heterogeneous across clusters. In the short-run, the impact of macroeconomic variables and digital infrastructure is more pronounced, underscoring the relevance of structural and contextual factors in shaping tourism dynamics. The findings emphasize the importance of aligning digital and educational policies with tourism development strategies while considering the structural differences among regions. This research provides a comparative framework that enhances the understanding of tourism as both an economic and social phenomenon.